Marketing for Hospitality and Tourism - Bowen John; Kotler Philip; Makens James (Prentice Hall, 1996)
Introduction: Marketing for Hospitality and Tourism, Social Foundations of Marketing: Meeting Human Needs, The Role of Marketing in Strategic Planning, Service Characteristics of Hospitality and Tourism Marketing, The Marketing Environment, Marketing Research and Information Systems, Consumer Markets and Consumer Buying Behavior, Organizational Buyer Behavior of Group Markets, Market Segmentation Targeting and Positioning, Designing and Managing Products, Internal Marketing, Building Customer Satisfaction Through Quality, Pricing Products: Pricing Considerations and Approaches and Strategy, Managing Capacity and Demand, Distribution Channels, Promoting Products: Communication and Promotion Policy, Promoting Products: Advertising and Direct Marketing and Sales Promotion, Promoting Products: Public Relations, Professional Sales, Destination Marketing, Next Year's Marketing Plan, References, Index.